NEGOSIASI NILAI-NILAI KEAGAMAAN DALAM PEMILIHAN KOSMETIK BAGI PEREMPUAN MUSLIM SALAFI YANG BELUM MENIKAH - Harisatun Naila Rofiah; Sujadi Sujadi (Jurnal Analisa Sosiologi, 2024)
This study examines how unmarried Salafi Muslim women navigate religious values in choosing cosmetics in the midst of modernity. The study uses an anthropological approach with in-depth interviews, participatory observation, and cultural artifact analysis. The findings show six main negotiation dimensions: (1) product halalness, (2) appearance in public spaces, (3) use of cosmetics at home and outside the home, (4) interaction with the cosmetics industry, (5) dependence on modern products, and (6) compatibility of cosmetics with worship. This dimension reflects a commitment to sharia while adjusting to social dynamics and modern aesthetics. Salafi Muslim women tend to prefer halal-certified cosmetics that fulfill the principle of tayyib (good and pure) and support the performance of worship. However, they face challenges, such as a lack of industry transparency, limited access to high-quality products, and social pressure to follow beauty trends. This study highlights the importance of collaboration between cosmetics manufacturers and halal certification bodies to improve product quality and transparency. This research provides new insights into the relationship between religion, culture, and consumption behavior, particularly in the context of Salafi Muslim women. Recommendations include quantitative research to expand the generalizability of the results and the development of more inclusive halal cosmetics. These results are relevant for global Muslim consumers and the cosmetics industry looking to respond to the needs of the halal market.